2022
DOI: 10.7759/cureus.29260
|View full text |Cite
|
Sign up to set email alerts
|

Tissue Healing in Hemicraniectomy

Abstract: Introduction Decompressive hemicraniectomy (DHC) is a last-resort treatment for refractory intracranial hypertension. Perioperative morbidity is associated with high risks of wound healing disturbances (WHD). Recently, a retromastoidal frontoparietooccipital (RMF) incision type was performed to avoid healing disturbance due to enhanced tissue flap perfusion compared to the classical reverse “question mark” (“Dandy flap”) incision. The goal of this study was to analyze the details of tissue healing p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…As noted by Fruh and colleagues, [ 13 ] this effect can secondarily enable performance of an anatomically appropriate DHC that allows for maximal decompression of the temporal base. Finally, Nertengian’s study reported the unique finding that the RA was associated with shorter operative times [ 15 ]. In summation, each of the studies comparing the RQM and RA reported positive benefits of the RA, and most reported decreased rates of postoperative wound infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As noted by Fruh and colleagues, [ 13 ] this effect can secondarily enable performance of an anatomically appropriate DHC that allows for maximal decompression of the temporal base. Finally, Nertengian’s study reported the unique finding that the RA was associated with shorter operative times [ 15 ]. In summation, each of the studies comparing the RQM and RA reported positive benefits of the RA, and most reported decreased rates of postoperative wound infection (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Nertengian's study reported the unique nding that the RA was associated with shorter operative times. 15 In summation, each of the studies comparing the RQM and RA reported positive bene ts of the RA, and most reported decreased rates of postoperative wound infection.…”
Section: Patient Demographics and Surgical Detailsmentioning
confidence: 96%
“…Following title and abstract screen as well as nal application of inclusion/exclusion criteria during full-text review, seven studies remained eligible for nal inclusion (Figure 1). Overall, there were six studies 10,[12][13][14][15][16][17] comprising Level III and one study that was Level IV evidence. On NOS risk of bias assessment, scores ranged from 3 to 8.…”
Section: Study Selection and Levels Of Evidence Of Included Studiesmentioning
confidence: 99%
“…Following title and abstract screen as well as nal application of inclusion/exclusion criteria during full-text review, seven studies remained eligible for nal inclusion (Figure 1). Overall, there were six studies 10,[12][13][14][15][16][17] comprising Level III and one study that was Level IV evidence. On NOS risk of bias assessment, scores ranged from 3 to 8.…”
Section: Study Selection and Levels Of Evidence Of Included Studiesmentioning
confidence: 99%